Exploring the phenotypic spectrum of desmoplakin cardiomyopathy. (25th November 2020) - Protonotarios, A; Cannie, D; Akhtar, M; Savvatis, K; Sekhri, N; Mohiddin, S; Lopes, L; Syrris, P; Elliott, P.M
Abstract: Introduction: Desmoplakin (DSP) gene mutations are reported to cause arrhythmogenic right ventricular cardiomyopathy (ARVC), but recent evidence suggests that they manifest as a much broader range of phenotypes. Purpose: To describe the phenotypic characteristics of DSP mutation carriers in a consecutive cohort of patients with heart muscle disease. Methods: A retrospective analysis of consecutive patients with heart muscle disease and their relatives that underwent diagnostic or research genetic testing. Only DSP variants classified as pathogenic by the American College of Medical Genetics and Genomics criteria were considered. Dilated cardiomyopathy (DCM), hypokinetic non-dilated cardiomyopathy (HNDC) and ARVC were diagnosed in accordance with current criteria. Results: 109 mutation carriers were identified: 34 (31%) had DCM and 23 (21%) HNDC. ARVC diagnosis was borderline and definite in 39 (36%) and 39 (36%) individuals, respectively. Sixteen (15%) presented with clinically suspected myocarditis. 23 patients met both definite AC and DCM criteria and 13 patients met definite AC and HNDC criteria. In 87 patients with cardiac magnetic resonance imaging, a spectrum of disease was observed (Table) including an intermediate phenotype characterised by subepicardial LV fibrosis in the absence of ventricular dilatation or dysfunction. Ventricular dysfunction was manifest as left dominant disease (n=22, 48%) and biventricular disease (n=24, 52%); none had right dominant disease. Conclusions: DSP mutations are associated with left and biventricular phenotypes and can present as myocarditis. Current ARVC and DCM diagnostic criteria inadequately describe the clinical subtypes of DSP related disease. A novel approach to disease classification is proposed. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): British Heart Foundation